2016
DOI: 10.1021/acs.est.6b01477
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of Direct and Indirect Exposure to Human Serum Concentrations of Perfluorooctanoic Acid in an Occupationally Exposed Group of Ski Waxers

Abstract: The contribution of direct (i.e., uptake of perfluorooctanoic acid (PFOA) itself) and indirect (i.e., uptake of 8:2 fluorotelomer alcohol (FTOH) and metabolism to PFOA) exposure to PFOA serum concentrations was investigated using a dynamic one-compartment pharmacokinetic (PK) model. The PK model was applied to six occupationally exposed ski waxers for whom direct and indirect exposures via inhalation were characterized using multiple measurements with personal air sampling devices. The model was able to predic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 46 publications
(26 citation statements)
references
References 64 publications
(186 reference statements)
1
25
0
Order By: Relevance
“…Our estimate of apparent half-life for PFOA is in the range of values reported from five studies with averages ranging from 2.3 to 3.94 years, observed in fluorocarbon workers 4 ; studies in populations living in PFOA-polluted areas around production plants, followed for 1–2 years after provision of clean drinking water 5 12 ; occupationally exposed ski waxers 13 ; and a study in a community exposed residentially to PFAS. 11 For PFOS, the population half-life has been estimated to be 4.3 years from studies in US blood donors reflecting general population reduction in exposure.…”
Section: Discussionmentioning
confidence: 51%
“…Our estimate of apparent half-life for PFOA is in the range of values reported from five studies with averages ranging from 2.3 to 3.94 years, observed in fluorocarbon workers 4 ; studies in populations living in PFOA-polluted areas around production plants, followed for 1–2 years after provision of clean drinking water 5 12 ; occupationally exposed ski waxers 13 ; and a study in a community exposed residentially to PFAS. 11 For PFOS, the population half-life has been estimated to be 4.3 years from studies in US blood donors reflecting general population reduction in exposure.…”
Section: Discussionmentioning
confidence: 51%
“…Current estimations for the half-life and volume of distribution used in several model approaches seem to be accurate, as indicated by successful model results in other studies. 18,34 In the presented model, the values of the serum elimination halflife and of the volume of distribution of PFOA, PFOS and PFHxS were taken from a study that successfully estimated serum concentration trends of PFOA and PFOS in adults. 35 Verner et al (2016) used slightly different values for the half-life and volume of distribution of PFOA and PFOS compared to the present work.…”
Section: View Article Onlinementioning
confidence: 99%
“…Beesoon et al (2011) analyzed 20 cord samples from manufacturing method for PFOA today, resulting in almost pure linear isomer. In addition to the environmental PFOA direct exposure, it has been hypothesized that the indirect exposure, such as the exposure of PFOA precursor, might be another important exposure route for the body burden of POFA (Gomis et al 2016). Experimental studies showed that precursor compounds uptake, like polyfluoroalkyl phosphate esters, a common food-contact paper packaging material, might be metabolized into PFOA in the body after uptake (D'eon and Mabury 2011; Vestergren et al 2008).…”
Section: Isomeric Profile Of Pfoa In Cord Serummentioning
confidence: 99%